Chromium stabilization and trapping in the cement matrix of recycled concrete aggregates. (10th December 2018) - Ben Maaouia, Oumeima; Hamzaoui, Rabah; Bennabi, Abdelkrim; Colin, Johan; Colina, Horacio
Highlights: The chromium presence in the aggregates of recycled concrete is analyzed. The potential leachability of the hexavalent chromium is studied. The recycling feasibility and the classification of the wastes is investigated. The stabilization of chromium in the cementitious matrix is confirmed. Abstract: Recycled concrete aggregates (RCA) originated from old deconstructed concrete may contain considerable amounts of heavy metals like chromium for example. In this work, we study the presence of chromium impact in the cementitious matrix of RCA, cement doped paste (OPC) and mortar with RCA (30% and 100% of RCA) from an environmental point of view. The leaching tests are carried out on monolithic and granular samples, using carbonated and non-carbonated RCA. Cr (VI) pH dependent leaching and Cr (VI) leaching mechanism have been studied. The experimental results has shown that aggregates are inert waste and can be used for road construction as substitution of original aggregates. Moreover, carbonation seems to have a positive effect on the decrease of the release of hexavalent chromium from the cementitious matrix. It was also confirmed that chromium is highly bound in the ettringite structure still present in the RCA matrix.